Misty the Cloud : a very stormy day - Dreyer, Dylan; Katz, Alan; Butcher, Rosie (New York : Random House, 2021)
"A young storm cloud learns to manage her big feelings when none of her friends can come out to play"--Provided by publisher
"Little cloud. Big feelings."--Cover
Keywords: Emotions -- Juvenile fiction